Video ethnography theory, methods, and ethics - Redmon, David (Routledge, Taylor & Francis Group, 2019)
Video Ethnography provides a thought-provoking, guided framework to ethnographic filmmaking. It examines how this kind of filmmaking can be a means of approximating, mediating and evoking lived experience. Functioning as a kind of sensory extension of the videographer, video ethnography arises directly out of lived experience as a process of dynamic encounters, mobile situations, and embodied approaches that include senses and choices of the videographer, and the participants of the ethnography. The book will help describe and develop students' sensibility and awareness of this crucial aspect of video ethnography, so they can craft their own video ethnographies with a fully conscious awareness of how certain skilled and attuned approaches to audiovisual techniques can help facilitate the fullest and most dynamic encounters possible. This book is suitable for classes in ethnographic filmmaking, video ethnography and visual anthropology / sociology